Microgeração de energia elétrica em uma propriedade rural utilizando biogás como fonte primária de energia elétrica - Marques, Cleber Aimoni (2012)
The energy is of fundamental importance to society, it is necessary for numerous activities of day-to-day, such as cooking, heating, refrigeration, lighting, among many others. Currently, with increasing population, the increasing use of industrial and agricultural machinery as well as fleet vehicles, there has been an increased demand for energy, especially fossil fuels renewable or not. Due to this growth, social and environmental problems arise because most of the sources used to produce fuel and electricity is produced from fossil fuels (oil, coal, natural gas), and burning these fuels releases various gases that are responsible for air pollution. Many countries have invested in the production of clean and renewable energy. This study aimed to evaluate the production of biogas from pig manure and generate electricity using biogas as a primary energy source. Biogas is produced on a farm located in São Miguel do Iguaçu / PR, which uses two digesters for biogas production, whose conversion into electricity is conducted in a motor-generator of 100 kVA or 76 kW. The biogas production data were collected using a gas meter model Roots Meter Series B3. For monitoring the consumption of biogas (m3 / h), the engine to generate electricity (kWh) used a mass flow transmitter of thermal dispersion model Thermatel TA2. The production of electricity (kWh) on the property was measured with a SMART METER T, which is a meter and recorder portable electrical quantities. For an average number of animals housed 4672 was 553 m3/day of biogas produced, making biogas used to generate 847 kWh / day of electricity. The average specific consumption of biogas in the engine 76 kW generator was 0.68 m3.kWh-1 and with an efficiency of 22.21%. The cost of producing electricity using the biogas was 0.45 R$ / kWh, on the other hand the value of energy paid by the concessionaire is 0.14 R$ / kWh, showing no viability. Moreover it was found that if there is a credit sale carbon and the increased production of biogas energy becomes competitive.